The ANALISIS FAKTOR-FAKTOR KEBERHASILAN WEBSITE BERITA ONLINE - Agatha Dinda Yosefani; Hansen Lim; Reita Austine Muliana; Mariesza Bengthie Cahyani; Maulidan Fazri (LPPM UNIVERSITAS BINA INSAN, 2025)
The shift in news consumption to digital platforms has brought about significant changes in the mass media landscape. This phenomenon has pushed many online news websites to continuously adapt to survive and excel amidst intense competition. Therefore, this study aims to identify and analyze the factors that contribute to the success of online news websites. This study uses a Systematic Literature Review by selecting 30 relevant articles. This analysis firmly found that technological developments, user behavior, and website design factors are variables that have a significant and fundamental influence on the success of news websites. The results of this analysis are expected to serve as reference material for online media managers, so that they can continue to carry out sustainable development in this digital era.